Microstructural investigation on engineered cementitious composites (ECC) - Too, Wee Jet (2015)
Engineered Cementitious Composites (ECC) is not only a kind of cementitious material with high performance, but also an engineered material that embodies a micromechanics-based design concept. To get ECC in reality, mix design is the very starting point. There is a missing link between factors of mix design and micromechanical parameters embedded in the micromechanical model of ECC. In this study, quite a number of experiments including single fiber pullout tests and matrix toughness tests were performed to fill the gap based on the theoretical analysis of micromechanical design guideline.